Comparative phylogeography and demographic histories of five widely distributed tropical eastern Pacific fishes. - Palmerín Serrano, Paola Nallely (2023)
The tropical eastern Pacific (TEP) has been divided into several biogeographic provinces separated by two types of habitat gaps: stretches of sandy shoreline that separate rocky reefs on the mainland (Sinaloan and Central American gaps) and expanses of deep ocean between offshore TEP islands and the mainland. Those gaps are known to influence the distribution and evolution of TEP reef fishes by acting as barriers to gene flow. We investigated potential effects of those gaps on the genetic structure and connectivity of populations of five widely distributed TEP reef-fish species that have different modes of life, habitat preferences and reproductive strategies: Caranx caballus, Rypticus bicolor, Hypsoblennius brevipinnis, Plagiotremus azaleus and Stegastes flavilatus. We used the coxI mitochondrial DNA marker to make phylogeographic, population genetics, and coalescent analyses of geographic patterns of genetic variation in these species. Those analyses showed high variation in levels of genetic diversity. We found no geographic genetic differentiation relating to mainland gaps in any species. Such genetic homogeneity may relate to factors such as migratory behavior, high pelagic dispersal potential and wide environmental tolerance. In two species, differentiation across oceanic gaps separating oceanic islands from the mainland may reflect differences between insular and mainland environments. Historical population expansions that occurred between 400 and 100 thousand years ago in different species may have shaped by patterns of Pleistocene climatic dynamics. The lack of polymorphism of coxI in the damselfish Stegastes flavilatus may relate to the effects of a historical population collapse, although we were not able to detect that genetically.